Green Marketing: A New Paradigm of Marketing in the Automobile Industry - Diwan, Saloni Pawan; Bodla, B. S. (Prabandhan: Indian Journal of Management, 2011)
In recent years, collective voices around the world to protect the ‘Planet Earth’ have become louder. The issues like depletion of natural resources, increasing environmental pollution and level of green house gases, deforestation in tropical areas, hole in ozone layer and global warming have attracted the attention of every government, business houses, non-government organizations and individuals. The concern about the environment has invited green movement worldwide. This green movement has necessitated green marketing practices, which aim at those business practices those do not adversely affect the environment. The present paper investigates the driving forces behind green marketing and the green marketing practices followed by the automobile industry. The study has brought out that the main approaches used by automobile industry are 3R (reduce, reuse and recycle), development of more energy efficient, environment-friendly products and natural resource conservation.